Shape-remodeled macrocapsule of phase change materials for thermal energy storage and thermal management - Yu, De-Hai; He, Zhi-Zhu (Applied energy, 2019)
•A shape-remodeled PCM macrocapsule was fabricated through a cast molding method.•The EBiInSn-based flexible shell can sustain a maximum stretching of 432%.•The prepared PCM macrocapsule can be remodeled as needed to a complicated shape.•An innovative PCM-based conformal thermal control method was demonstrated.•The thermoelectric generation module based on PCM macrocapsule was developed. This paper reports on a novel phase change material macrocapsule for thermal energy storage, which can be dynamically and repeatably remodeled as needed to a complicated shape with large-scale deformation. In addition, it effectively eliminates the stress mismatch, induced by the volumetric expansion (or shrink) of the phase change material during melting (or solidification), through the self-adaptative deformation of the coated flexible shell. The shape-remodeled macrocapsule, consisting of octadecanol as the core and the silicone elastomer for encapsulation, was prepared through a cast molding method. The high-concentration microparticles of low-melting Bi-In-Sn eutectic alloys were embedded into elastic shell for significantly enhancing its latent heat storage and heat conductivity. The prepared macrocapsule has a high latent heat density of 210.1 MJ/m3, which of the contribution from the shell is about 20%. The thermal conductivity of the macrocapsule core reaches to 1.53 W/m·K with a 428% increase compared with pure octadecanol. The flexible shell attains a high thermal conductivity of 1.98 W/m·K with an 890% increase compared with pure silicone, which also remains a high stretchability with 432% strain. The performance of shape remodeling, energy storage capacity, and heat charging and discharging rates of the macrocapsule were demonstrated in detail. The applications of the prepared macrocapsule as thermal management for the flexible electronic devices and the thermal storage for thermoelectric energy harvesting were also investigated. The present study opens the way for further development of elastic phase change material capsule applications in energy storage systems and thermal control engineering.